Manajemen SDM Berbasis Teknologi sebagai Strategi Peningkatan Kompetensi Guru - Restu Resky Satriya; Ida Rindaningsih (Maeswara : Jurnal Riset Ilmu Manajemen dan Kewirausahaan, 2024)
The application of technology-based human resource (HR) management in education is becoming increasingly important to enhance the quality of management and the development of teachers’ competencies. Technology, particularly through the use of Management Information Systems (SIM) and Learning Management Systems (LMS), enables more efficient data management and flexible professional development for teachers. However, its implementation faces key challenges such as limited infrastructure and low digital skills among some teachers. This study uses the Systematic Literature Review (SLR) method to analyze relevant sources in order to identify the role of technology in HR management in education and the challenges faced in its implementation. The findings show that the application of technology in HR management in education has a positive impact on efficiency and teacher competence. However, the biggest challenges are limited infrastructure and digital skills of teachers. Policies supporting infrastructure improvements and digital training for teachers are necessary to ensure that technology can be optimally used to improve the quality of education in Indonesia.